Peran Ekstrak Tanaman Herbal Dalam Mengendalikan Tekanan Darah Pada Penderita Hipertensi - Agiska Nada Berliana Sari; Aurora Nabinkha Putri Ismail; Farah Nur’aini Ramadhanti (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Hypertension or what is also called high blood pressure is a medical condition where a person's blood pressure is at a high level. This condition is characterized by systolic pressure exceeding 140 mmHg and diastolic pressure exceeding 90 mmHg. Treatment for hypertension includes pharmacological and non-pharmacological treatment. Non-pharmacological treatments such as exercise, maintaining diet, and non-drug therapy through the use of herbal ingredients. In this era of globalization, there are still people who choose to consume medicinal plants rather than consuming chemical treatments. This research aims to review various types of plants that can be an alternative treatment for hypertension. The method used is a literature study via Google Scholar. Based on the results of a literature study, several journals were found that discussed plants that can treat hypertension, such as starfruit, green tea, African leaves, suruhan herbs, garlic, and celery leaves. This is because these plants contain flavonoids, saponins, and tannins which can control blood pressure.